Cameron Shopping Center (1959)
View of the parking lot at Cameron Shopping Center, Palm Springs, CA, 1959. A Mayfair Market with is also visible, along with mountains in the background. Stamped "Bethlehem Steel (PCD) NEG. NO. 59738-1" on back.